Clinical Profile of Neurological Disorders in Children (Bangladesh Journal of Medical Science, 2011)
A study was done on 110 children in the age group of 1 month to 12 years admitted with neurological problems in the Dept. of Paediatrics, IPGMR, Dhaka from September 1993 to August 1994. The aim of the study was to find out neurological disorders of children and to investigate the quality of neurodiagnostic services presently available. These 110 neurological cases comprised of 8.9% of the total admission during this period. Of the 110 patients 69.10% (76) patients were male and 30.90% (34) female with a male-female ratio of 2.23%:1. 50% (55) of the patients were under two years of age. Majority of the neurological disorders were meningitis (24.55%) and cerebral palsy (21.91%). Febrile convulsion was present in 15 patients (13.64%). Other neurological problems were Encephalitis (7.27%), Epilepsy (8.81%), Hydrocephalus (3.36%), Guillain-Barré syndrome (5.45%), Brain Tumours (3.65%), Post-Polio Paresis (3.65%), Cerebral Infarction (1.82%) and others. Among 27 children with meningitis 11 cases were pyogenic, 12 cases tubercular and 4 cases were aseptic. Of the 23 cerebral palsy children 6 were due to birth asphyxia and 6 were post meningitis and in the rest 11 the cause could not be ascertained. CT scan of the brain was an effective method of investigation to determine the patholocal lesions. Only one patient (0.9%) suffering from cerebellar haemorrhage expired among these 110 patients. This study emphasized the need for a comprehensive, preventive, better neurodiagnostic service and timely management of neurological cases.DOI: http://dx.doi.org/10.3329/bjms.v3i1.8223BJMS 1996; 3(1): 21-26